Roquin exhibits opposing effects on RNA stem-loop stability through its two ROQ domain binding sites - Jan-Niklas Tants; Andreas Walbrun; Lucas Kollwitz; Katharina Friedrich; Matthias Rief; Andreas Schlundt (Proceedings of the National Academy of Sciences, 2025)
The interaction of mRNA and regulatory proteins is critical for posttranscriptional control. For proper function, these interactions, as well as the involved protein and RNA structures, are highly dynamic, and thus, mechanistic insights from structural biology are challenging to obtain. In this study, we employ a multifaceted approach combining single-molecule force spectroscopy (SMFS) with NMR spectroscopy to analyze the concerted interaction of the two RNA-binding interfaces (A-site and B-site) of the immunoregulatory protein Roquin’s ROQ domain with the 3’ untranslated region (UTR) of the Ox40 mRNA. This 3’UTR contains two specific hairpin structures termed constitutive and alternative decay elements (CDE, ADE), which mediate mRNA degradation through Roquin binding. Our single-molecule experiments reveal that the CDE folds cooperatively, while ADE folding involves at least three on-pathway and three off-pathway intermediates. Using an integrated microfluidics setup, we extract binding kinetics to Roquin in real time. Supported by NMR data, we find opposing effects of the two Roquin subdomains on distinct regions of the ADE: While the A-site interacts strongly with the folded apical stem-loop, we find that the B-site has a distinct destabilizing effect on the central stem of the ADE owed to single-strand RNA binding. We propose that RNA-motif nature and Roquin A- and B-sites jointly steer mRNA decay with context-encoded specificity, and we suggest plasticity of stem structures as key determinant for Roquin–RNA complex formation. The unique combination of NMR and SMFS uncovers a mechanism of a dual-function RNA-binding domain, offering a model for target RNA recognition by Roquin.